Hepatoprotective Activity of Aqueous Extract of Sesbania grandiflora Linn Leaves against Carbon Tetrachloride induced Hepatotoxicity in Albino Rats - Dayananda Bhoumik,; Arunabha Mallik,; Abera Hadgu Berhe, (International Journal of Phytomedicine, 2016)
The present study was conducted to evaluate the hepatoprotective activity of aqueous extract of leaves of Sesbania grandiflora Linn (AESG) at the dose of 250 and 500 mg/kg body weight per oral using Carbon tetrachloride induced liver damage in wistar albino rats. Aqueous extract showed significant (p<0.05) hepatoprotective effect by lowering the serum levels of various biochemical parameters such as serum glutamic oxaloacetate transaminase (SGOT), serum glutamic pyruvates transaminase (SGPT), alkaline phospatase (ALP), total bilirubin (TBL), total cholesterol (CHL) and by increasing the levels of total protein (TPTN) and albumin (ALB), in the selected model. These biochemical observations were inturn confirmed by histopathological examinations of liver sections and were comparable with the standard hepatoprotective drug Silymarin (100 mg/kg body weight i.p.) which served as a reference control. It was concluded from the result that the aqueous extract of Sesbania grandiflora L. possesses hepatoprotective activity against Carbon tetrachloride induced hepatotoxicity in rats.